Analisis Faktor-Faktor yang Mempengaruhi Pembiayaan Bermasalah Pada Bank Syariah di Indonesia dengan Pendekatan Error Correction Model (ECM) - Mohammad Dendi Abdul Nasir; Nunuk Khomariyah (Iqtishodia: Jurnal Ekonomi Syariah, 2020)
This research aims to analyze the influence of internal factors (asset and financing deposit ratio) and external factors (inflation and exchange) against Non Performing Financing (NPF) to Syariah Bank in Indonesia. This research was quantitatif, used a secondary data sourced from Indonesian Bank in Januari 2011 to June 2018. The data analyzed with statistic method using Error Correction Model (ECM). The result found that in the Financing to Deposit Ratio (FDR) variable of Syariah Bank has a significant impact on the NPF, while asset variable, inflation and exchange are not have a significant impact. While in the long term, asset variable and inflation has a significant impact to Syariah Bank NPF, the FDR variable and exchange are has not a significant impact.